Supramolecular Architectures Based on the Self-Assembly of Suberin Hydrolysate, Betulin, and Their Hybrids - Farooq, Muhammad; Zborowski, Charlotte; Nousiainen, Paula A.; Tienaho, Jenni; Korpinen, Risto; Österberg, Monika (American Chemical Society, 2025)
Self-assembly offers a promising approach for producing functional nanomaterials from renewable biomass sources, as demonstrated in this study investigating two hardwood birch (Betula pendula Roth) bark extractives: suberin hydrolysate (SH) and betulin fraction (BF). Using solvent inversion self-assembly with acetone, ethanol, and γ-valerolactone as solvents and water as an antisolvent, we prepared nanoparticles with tunable properties. Comprehensive characterization using FESEM image analysis revealed that SH formed predominantly rod-like structures (77–587 nm), while BF formed spherical particles (14–74 nm), with morphologies significantly influenced by solvent type and concentration. Coassembly of SH and BF (1:1) resulted in unique hybrid star-shaped nanoparticles, exhibiting both rod-like and spherical features. All nanoparticles demonstrated hydrophobic properties, with BF crystals achieving superhydrophobic surfaces (water contact angle 162° ± 8°) and BF NPs showing excellent water repellency (153° ± 2°) and maintaining water droplet shape without absorption for over 30 min. The nanoparticles showed significant antimicrobial efficacy against Gram-positive bacteria S. aureus, with SH NPs demonstrating the highest inhibition. XRD analysis revealed that the self-assembly process enhanced crystallinity for both SH and BF, contributing to their improved functional properties. The ability to achieve such precise control over nanoparticle assembly of these heterogeneous, renewable biomass extractives represents a significant advancement in sustainable nanomaterial development, making them particularly suitable for functional coating applications.
Keywords: crystals; ketones; nanoparticles; self organization; solvents